Perfil clínico e epidemiológico de pacientes idosos com doença de chagas atendidos no serviço de atenção farmacêutica, entre 2005 a 2013, no Ceará - Pereira, Laíse dos Santos (2014)
As the control of the vectorial and transfusional transmissions of Chagas disease (CD) progressed, cases of young people with the infection have become rare, causing a rise in the average age of patients, leading to the emergence of an elderly population with the chronic infection. Thus, the challenge of providing assistance to this group of patients that are in this unfavorable condition remains to the Public Health System. In this context, the present study aimed to characterize the clinical and epidemiological profile of elderly patients with CD followed at the Pharmaceutical Care Service of the Chagas Disease Research Laboratory of the Federal University of Ceará (LPDC / UFC). This was a descriptive cross-sectional survey, in which the information related to demographic, socioeconomic, medication use, comorbidities associated with CD and habits of life of all patients aged ≥ 60 years followed at the Service between 2005-2013 were evaluated. To characterize the clinical form of CD, the medical records of patients were provided by the Walter Cantídio University Hospital (HUWC). From 411 patients followed at the Service in the period of the study, 97 (23.6%) were elderly. The percentage distribution of elderly in relation to the total number of patients registered in the Service increased significantly (p = 0.003) from 12.9% between July/2005-June/2009 to 29.0% between July/2009-June/2013. The profile of the studied population was: women (50.5%); mean age of 66,9±6,5 years; retired (54.6%); family income of 1 minimum wage (51.5%); incomplete primary education (49.5%) and illiterate (40.2%); coming from the Low Jaguaribe Microrregion (62.9%). The predominant clinical form was the cardiac (65.3%) and 13.7% of patients presented cardiac form associated with digestive form, mainly megacolon. The major electrocardiographic changes found were: right bundle branch block (RBBB) (41.0%), anterosuperior left bundle branch block (ASDB) (27.4%), changes in ventricular repolarization (CRV) (16.8%) and ventricular extrasystole (VES) (13.9%). Eighty four patients (86.6%) reported at least one disease associated with the CD, with a mean of 2.23 ± 1.54 comorbidities per patient. The most frequent were: systemic arterial hypertension (SAH) (67%), dyslipidemia (32.0%), dyspepsia (16.5%) and diabetes mellitus (14.4%). A positive correlation was found between the variables sex and comorbidity. The SAH was found as a risk factor for the development of Chagas heart disease (OR = 4.125, CI = 1.47-11.56). It was observed in the present study that the growth of the elderly population with CD is a reality. Therefore, it is concluded that this vulnerable group of patients associate the aging process with cardiac and/or digestive changes that result from evolution of the CD, as well as with other comorbidities, which requires special attention from health services to more appropriate medical and social care.